Analysis of Factors Influencing Farmers' Interest in Applying Bioinsecticides to Control Brown Planthoppers in Pendowoharjo Village: Analisis Faktor-Faktor yang Memengaruhi Minat Petani dalam Penerapan Bioinsektisida untuk Pengendalian Wereng Batang Coklat di Kalurahan Pendowoharjo - Meriana Novita; Agus Wartapa; Sujono (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
Brown planthopper (Nilaparvata lugens) infestation remains a major constraint to rice production in Indonesia, highlighting the need for environmentally friendly pest management through bioinsecticides. This study aimed to analyze factors influencing farmers' interest in adopting bioinsecticides for brown planthopper control. Conducted in Pendowoharjo Village, Bantul Regency, Yogyakarta, the research involved members of the Subur Farmer Group with a population of 52 farmers. A total of 46 respondents were selected using simple random sampling. Primary data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results revealed that education, farming experience, extension worker role, and government support simultaneously had a significant effect on farmers' interest, with an R² value of 0.773 (77.3% of variation explained). Partially, education (B=0.321; p=0.024), farming experience (B=0.425; p=0.005), and government support (B=0.311; p=0.044) had positive and significant effects, while extension worker role (B=0.054; p=0.722) was not significant. Farming experience was the most influential factor. These findings indicate that farmers' internal capacities and institutional support play crucial roles in promoting the adoption of environmentally friendly pest control innovations. However, the findings are limited to a single farmer group context, so broader generalization should be made with caution.